Higher Education in the Midst of a Pandemic: A Dean’s Perspective - Rowley, William J. (International Dialogues on Education Journal, 2020)
This paper suggests changes that are likely to occur in higher education resulting from the coronavirus pandemic from a retired dean’s perspective. Global events like the Great Depression and World War II led to significant societal and cultural changes. This global pandemic will have the same impact. Higher education will not be the same in the future. What makes it difficult to predict its future is the fact that colleges and universities have no predetermined guidelines for how to offer an entire academic program during a worldwide health crisis. Administrators are having to figure out how to respond on the fly. This isn’t to say there is no future for higher education. However, no colleges or universities will be able to conduct business as usual. For those who survive this changed environment, a significant re-assessment of every aspect of its enterprise will be required. This will include financial viability, mission, academic programs, program delivery, technology, library and student services.